Nabiximols in Chronic Neuropathic Pain: A Meta-Analysis of Randomized Placebo-Controlled Trials. Issue 4 (9th February 2021) - Dykukha, Igor; Malessa, Rolf; Essner, Ute; Überall, Michael A
Abstract: Objective: Pooled analysis of nabiximols and placebo in randomized controlled studies (RCTs) of chronic neuropathic pain. Design: Systematic review and meta-analysis. Methods: A systematic literature search was conducted to identify double-blind placebo-controlled RCTs of nabiximols for chronic neuropathic pain. The clinical endpoint of interest was change from baseline in mean pain score on 11-point numerical rating scales. Mean difference (MD) and standardized mean difference (SMD, Hedges' g) were calculated using fixed effect (FE) and random effects (RE) models. Strength of evidence was assessed using the Cochrane Grading of Recommendations Assessment, Development and Evaluation (GRADE) tool. Risk of bias was assessed using the revised Cochrane risk-of-bias tool (RoB 2). Results: Nine RCTs with 1289 participants were included. Quality of evidence (GRADE) was moderate. One study had a high risk of bias (RoB 2) and five had some concerns. For the pooled endpoint of change from baseline in mean pain score, nabiximols was superior to placebo, with a MD of −0.40 (95% confidence interval [CI]: −.59 to −.21; FE, P < .0001) or −0.44 (95% CI: −.70 to −.19; RE, P = .0006). A SMD of −0.21 (95% CI: −.32 to −.10; FE) or −0.26 (95% CI: −.42 to −.10; RE) indicated an incremental benefit over background analgesia. Results in favor of nabiximols were maintained in sensitivity analyses. Conclusions: Nabiximols was superior to placebo for reduction of chronic neuropathic pain, with a small effect size. Larger RCTs designed to assess the effect of nabiximols in neuropathic pain are required to reach more definitive conclusions.